Travailler à haute voix sur Twitter - Claudine Bonneau (Tic & Société)
Nowadays, a growing number of organizations implement corporate social network tools intended for internal use. However, work-related conversations also circulate on “public” (i.e. external) social media sites. Scholars studying collaborative practices in the workplace need to take this public channel in consideration, even if it is neither recognized, authorized nor controlled by the employer. Twitter, for example, is a microblogging site used by some workers to share not only their tacit or formal knowledge, but also to make hypotheses, intentions, reflections, problems and questions visible in real time outside the formal boundaries of the organization. Even though Twitter was not originally created as a conversational or collaboration platform, we observe different form of informal collaboration practices involving the use of this tool by employees who have decided to integrate it in their professional lives. This article presents empirical examples illustrating the following types of uses: “working out loud” narratives, sharing traces of “work-in-progress,” broadcasting intentions and asking questions of the crowd.